1) -5
2) 0,8
3)
Пошаговое объяснение:
1) 4(1-0,5а) = -2(3+2а)
4-2а = -6-4а
2а = -10
а = -5
2) 5(х+1,2) = 12,5х
5х+6 = 12,5х
7,5х = 6
х = 0,8
3) (4-3х) = 1х-
2-1х = 1х-
3х = 2
х =
1) -5
2) 0,8
3)![\frac{5}{6}](/tpl/images/1194/8906/2bbce.png)
Пошаговое объяснение:
1) 4(1-0,5а) = -2(3+2а)
4-2а = -6-4а
2а = -10
а = -5
2) 5(х+1,2) = 12,5х
5х+6 = 12,5х
7,5х = 6
х = 0,8
3)
(4-3
х) = 1
х-![\frac{1}{2}](/tpl/images/1194/8906/9cdae.png)
2-1
х = 1
х-![\frac{1}{2}](/tpl/images/1194/8906/9cdae.png)
3х = 2![\frac{1}{2}](/tpl/images/1194/8906/9cdae.png)
х =![\frac{5}{6}](/tpl/images/1194/8906/2bbce.png)